Decision Support System for Determination of Water Supply Distribution Decisions Using the Technique for Order Preference Method by Similarity to Ideal Solution (TOPSIS) - Henrycus Baik Handoko (Institute of Computer Science (IOCS), 2021)
The Water Supply Decision Support System is a computer-based information system that can be used to help support the quality of human life in terms of providing clean water. In this system, the results will be in the form of priority decisions for the provision of clean water for each candidate area. In the Social Service Office of Sragen Regency itself, there are criteria in determining decisions according to the results of the proposals submitted by each regional candidate including the number of families who need clean water (KK), the number of people in each region (SOUL), the number of water drops in each region (TANK), and the number of hamlets that need clean water in each area (DUKUH). TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) is the method used in this system, determine the results of relative proximity to the ideal solution so that it can produce priority values ​​from several areas. This method was chosen because it considers the distance to the positive ideal solution and the distance to the negative ideal solution by taking relative proximity to the positive ideal solution. Based on the comparison to the relative distances, an alternative priority arrangement can be reached. Based on the comparison to the relative distances, an alternative priority arrangement can be reached. From the results obtained, it can be used to help procure clean water to areas that meet priorities, and its nature only helps to find priority values ​​according to relative proximity to the ideal solution and is not the final goal for decision making. This method was chosen because it considers the distance to the positive ideal solution and the distance to the negative ideal solution by taking relative proximity to the positive ideal solution. Based on the comparison to the relative distances, an alternative priority arrangement can be reached. From the results obtained, it can be used to help procure clean water to areas that meet priorities, and its nature only helps to find priority values ​​according to relative proximity to the ideal solution and is not the final goal for decision making.